2017
DOI: 10.1097/iae.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Patients With Retinitis Pigmentosa Type 12 Caused by Crb1 Mutations

Abstract: The wide and variable clinical spectrum in patients with the same CRB1 mutation supports the hypothesis that the CRB1 type autosomal recessive retinitis pigmentosa-phenotype is modulated by other factors. The clinical variability will make it harder to evaluate the effect of (upcoming) therapies for retinitis pigmentosa, although because of the intraindividual similarity between both eyes, the contralateral eye can be used as an excellent internal control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 34 publications
9
34
3
Order By: Relevance
“…These ages scan shows small hyperreflective outer retinal accumulations right above the retinal pigment epithelium (RPE) that seem to correspond with a reticular pseudodrusenoid-like aspect on funduscopy (Fig 2E). are comparable with those reported by Mathijssen et al, 17 who found median ages of 18 and 35 years for reaching a VA of 0.3 or less and 0.1 or less, respectively. When testing for statistical difference between the survival curves, we found no significant difference between the GI patients and the non-GI patients in this study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These ages scan shows small hyperreflective outer retinal accumulations right above the retinal pigment epithelium (RPE) that seem to correspond with a reticular pseudodrusenoid-like aspect on funduscopy (Fig 2E). are comparable with those reported by Mathijssen et al, 17 who found median ages of 18 and 35 years for reaching a VA of 0.3 or less and 0.1 or less, respectively. When testing for statistical difference between the survival curves, we found no significant difference between the GI patients and the non-GI patients in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Optic disc drusen in this GI population carrying a homozygous p.(Met1041Thr) mutation in CRB1 previously were reported in similar numbers. 5,17 We found no optic disc drusen in the non-GI patients. Interestingly, optic disc drusen have been reported in patients with different CRB1 genotypes.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations